Adverse outcomes of perioperative red blood cell transfusions in coronary artery bypass grafting in Hospital Universiti Sains Malaysia - Hua, Chan Choon (2020)
Background: Perioperative red blood cell (RBC) transfusion in coronary artery bypass grafting (CABG) has both benefits and harms. Our aim was to study the association between perioperative RBC transfusion and its adverse outcomes in patients who underwent isolated CABG. Methods: This was a retrospective record review of patients who underwent isolated CABG in Hospital Universiti Sains Malaysia, Kelantan, Malaysia from 1 January 2013 until 31 December 2017. Data were collected from medical records, and comparisons were made between patients who received perioperative RBC transfusions and those who did not with their adverse outcomes after CABG. Results: A total of 108 patients who underwent isolated CABG were included in our study, and 78 (72.2%) patients received perioperative RBC transfusions while 30 (27.8%) patients did not. After CABG, patients who received perioperative RBC transfusions compared to those who did not, were significantly more likely to develop prolonged ventilatory support (21.8% vs. 0%, p = 0.003), cardiac morbidity (14.1% vs. 0%, p = 0.032), renal morbidity (28.2% vs. 3.3%, p = 0.005) and serious infection (20.5% vs. 3.3%, p = 0.037). With each unit of packed RBC transfusions, there was a significantly increased risk of prolonged ventilatory support (adjusted odds ratio [AOR] = 1.45; 95% confidence interval [CI] = 1.20 - 1.77; p < 0.001), cardiac morbidity (AOR = 1.40; 95% CI = 1.01 - 1.79; p = 0.007), renal morbidity (AOR = 1.23; 95% CI = 1.03 - 1.45; p = 0.019) and serious infection (AOR = 1.31; 95% CI = 1.07 - 1.60; p = 0.009). Conclusion: Perioperative RBC transfusion in isolated CABG patients is associated with increased risks of developing adverse events such as prolonged ventilatory support, cardiac morbidity, renal morbidity and serious infection